3. A CASE REPORT: A CHILD WITH Hymenolepiasis AT NATIONAL INSTITUTE OF MALARIOLOGY, PARASITOLOGY, AND ENTOMOLOGY (Vietnam Journal of Community Medicine, 2025)
Background: Hymenolepiasis is caused by two species of tape worm: Hymenolepis nana (the dwarf tapeworm) and Hymenolepis diminuta (rat tapeworm). Hymenolesis spp. damages the villi of the small intestine and ileum, especially children. Hymenolepiasis spp. is a globally prevalent zoonosis, especially tropical, subtropical and temperate zones. The disease by Hymenolepis nana (H. nana) is transmitted through two cycles, which are the direct cycle by the fecal-oral route, when people eat foods containing H. nana eggs, or the autoinfection cycle, when the host is infected with H. nana, the eggs do not pass out in the feces and hatch in the host's intestine, develop into adults and cause disease. The disease by Hymenolepis diminuta (H. diminuta) is transmitted through the indirect cycle by swallowing arthropods containing H. diminuta larvae. The disease by Hymenolepis spp. causes damage to the villi of the small intestine and ileum, especially in children.Case presentation: A 7-year-old boy whole lives in Dien Chau district, Nghe An province. One month before being admitted to the hospital, he had clinical symptoms of anorexia, slight weight loss, and intermittent periumbilical discomfort. The child did not have the hands washing habit before eating. The examination of concentrated stool samples found Hymenolepis spp. eggs. Patient was succcessfully treated with praziquantel at a single dose of 25 mg/kg body weight.Conclusion: Human infections with Hymenolepiasis spp. is very rare that can be overlooked because it often does not have typical clinical symptoms. Clinicians need to pay attention when encountering children, who are less likely to have the habit of washing their hands before eating, having  clinical symptoms such as loss of appetite, weight loss,  abdominal pain, they are needed to do a stool test to find Hymenolepis spp. eggs as soon as possible for early diagnosis and prompt treatment.
Keywords: Hymenolepiasis; Hymenolepis nana; Hymenolepis diminuta; praziquantel